Pandangan Dunia Yi Munyol dalam Novel Our Twisted Hero - Elkhoiriyah, Mar’ah Mukhbita (Universitas Gadjah Mada, 2023)
This study aims to find the author's worldview on the novel, Our Twisted Hero. The worldview is examined using Lucien Goldmann's genetic structuralism theory which views a literary work from the structure that builds it. The structure is in the form of homology between the structure of the novel and the social structure in society. According to Goldmann, the structure of the novel is centered on the relationship between characters and between characters with objects. The author's social group is also a material consideration behind the formation of his worldview. The result of this research shows the author's view toward struggle for democracy in South Korea in the 1980s including the attitude of the people involved. Through the conflict between the problematic hero Han Byeongtae and Eom Seokdae, his classmate, and homeroom teacher, this research reveals the view of the author who thinks that the lack of concern for some people towards the struggle for democracy actually helps authoritarian governments strengthen their power. However, the author's main goal is not to judge the right or wrong of it but to reveal the hard reality that actually happened back then through Yi Munyol's point of view as the author of the novel.